209k views
4 votes
If 9a +8b+9c=-9 , what is 81c+72b+81a ?

2 Answers

4 votes
ok so given
9a + 8b +9c =-9
&
81c +72b +81a
now i rearrange the terms (since addition is commutative)
81a +72b +81c
what is this equal to?

well comparing the first and 2nd equation
9a + 8b + 9c = -9
81a +72b +81c =?

well compare 9a to 81a? is there something you can multiply to the first to get the 2nd
compare 8b to 72b, can you use that same number to get 2nd
same for 9c to 81c

you would probably notice that by multiplying them all by 9, you will get the terms in the 2nd expression

so, if you multiply each term in the first to get the 2nd, wouldnt the answer of the 2nd be the 1st multiplied by 9?
User Michiel Cornille
by
5.8k points
7 votes
9x9=81
8x9=72
9x9=81
-9x9=-81
User ToastedSoul
by
5.8k points